Iowa Birdline update, August 23, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email of the Iowa Birdline update for August 23, 1993. Highlights include reports of some interesting shorebirds. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed